PO-51 - Expression of proteins of the tissue factor thrombin pathway is upregulated in the stroma and epithelium of colorectal cancer. Issue 140 (April 2016) - Clouston, H.W.; Davenport, A.; Gregson, H.; Shaker, H.; Duff, S.; Kirwan, C.C.
Abstract : Introduction: Colorectal cancer expression of Tissue Factor (TF), PAR1 and PAR2 is associated with a poor prognosis. Their stromal, rather than epithelial, expression has prognostic significance in other cancers, this has not been explored in colorectal cancer. Aim: We aimed to determine the expression patterns of Tissue Factor (TF), PAR1 and PAR2 and thrombin in colorectal cancer and normal tissue. Materials and Methods: Cancer and distant normal tissue were sampled from 37 patients. Expression of TF, Thrombin, PAR1 and PAR2 were determined by immunohistochemistry. Two observers scored expression level (0–3) in individual cells. Percentage of cells having each level of expression was determined and an H-score calculated which are given with 95% CI. Results: Normal epithelium did not express TF, but it was expressed by cancer epithelium (36.5 (95% CI 17.6 – 55.4) p < 0.001). Thrombin expression was increased in cancer vs normal epithelium (126.2 (95% CI 110.6 – 141.7) vs 101.6 (95% CI 92.5–110.8) p = 0.01) as was PAR2 (172.4 (95% CI 152.9–191.8) vs 123.4 (95% CI 107.8–139.0) p < 0.001). The increase in cancer epithelium PAR1 expression compared to normal (105.4 (95%CI 84.3–126.5) vs 89.0 (95% CI 80.4–97.6)) was not significant. Normal stroma did not express TF or thrombin however both were expressed by cancer stroma (TF 46.3 (95% CI 24.6–68.0) p < 0.001, thrombin 11.4 (95% CI 6.2–16.7) p < 0.001). PAR1 and PAR2 were both expressed in normal stroma but demonstrated increased expression in cancer stroma (cancer vs normal; PAR 1: 130.7 (95% CI 112.2–149.2) vs 19.5 (95% CI 11.24–27.7) p < 0.001; PAR2: 21.5 (95% CI 12.9–30.1) vs 2.21 (95% CI 0.49–3.92) p < 0.001). Conclusions: Upregulated expression of tissue thrombin pathway proteins is seen in colorectal cancer in both epithelial and stromal cells. Procoagulant tumour cells and tumour microenvironment may provide a novel therapeutic target for treatment in colorecal cancer.